2016
DOI: 10.1007/s00277-016-2668-0
|View full text |Cite
|
Sign up to set email alerts
|

Bendamustine plus rituximab versus R-CHOP as first-line treatment for patients with indolent non-Hodgkin’s lymphoma: evidence from a multicenter, retrospective study

Abstract: The optimal first-line treatment for advanced low-grade non-Hodgkin lymphomas (LG-NHL) is still highly debated. Recently, the StiL and the BRIGHT trials showed that the combination of rituximab and bendamustine (R-B) is non-inferior to rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) with a better toxicity profile. Utilizing a retrospective analysis, we compared the efficacy and safety of both regimens in clinical practice. From November 1995 to January 2014, 263 LG-NHL patients t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 18 publications
3
20
0
2
Order By: Relevance
“…That statement is well supported by the observation that our clinical results are superimposable to those from other larger and pivotal trials: in particular, in our series CR rate resulted 79%, 2-years PFS 85%, and 2-years OS 94%. These values result comparable to those recently reported by Mondello et al in 192 cases randomized to receive R-bendamustine or R-CHOP (Mondello et al, 2016). Those authors reported the superiority of R-bendamustine, with a significant prolongation of the median PFS (152 vs. 132 months); in that study, bendamustine offered 94% of ORR, and 63% of CR.…”
Section: Discussionsupporting
confidence: 91%
“…That statement is well supported by the observation that our clinical results are superimposable to those from other larger and pivotal trials: in particular, in our series CR rate resulted 79%, 2-years PFS 85%, and 2-years OS 94%. These values result comparable to those recently reported by Mondello et al in 192 cases randomized to receive R-bendamustine or R-CHOP (Mondello et al, 2016). Those authors reported the superiority of R-bendamustine, with a significant prolongation of the median PFS (152 vs. 132 months); in that study, bendamustine offered 94% of ORR, and 63% of CR.…”
Section: Discussionsupporting
confidence: 91%
“…In the case of transformation into an aggressive lymphoma, R-CHOP is considered the standard of care [53]. As previously reported [23,25], the observed PFS prolongation did not translate into a OS advantage of R-B over R-CHOP. This could be because of the indolent clinical course of FL even after a relapse and the availability of efficient salvage treatments.…”
Section: Discussionmentioning
confidence: 66%
“…In both trials, the positive impact of R‐B was independent from other prognosticators such as age, lactate dehydrogenase (LDH) levels, and the follicular lymphoma international prognostic index (FLIPI). Moreover, these positive results were confirmed in a real‐life analysis . However, until now, no published data comparing R‐CHOP with R‐B as a first‐line treatment in patients affected by FL3A were available.…”
Section: Introductionmentioning
confidence: 74%
“…Bendamustine is a bifunctional drug that acts as an alkylating and antimetabolite agent with no or little renal clearance . In patients with iNHL, the hematological response following BR reaches 80–90% (complete response 40%‐60%) . Unlike RCD, the lack of steroids with BR may be of interest to patients with diabetes mellitus, chronic kidney disease, or to reduce the risk of infection.…”
Section: Introductionmentioning
confidence: 99%